Critical analysis and assessment of language policy and implementation in South Africa: South African Broadcasting Corporation’s Soap Operas - Aiseng, Kealeboga (My University, 2024)
South Africa is a country with a heavy political past, having gone through colonialism, and Apartheid. The country’ history brewed ideologies of exclusion and inclusion, empowerment, and disempowerment. Among these were linguistic issues. In 1994, South Africa officially became a democratic country, with a new Constitution adopted in 1996. The South African Constitution is globally recognised for its principles of freedom, equality, reconciliation, and multiculturalism. Post-Apartheid South Africa also saw the significant role that can be played by popular culture in redressing the mistakes of the past. Hence, popular culture in post-Apartheid South Africa was given a task of healing the wounds of the past and building a united South Africa. The problem, however, is that linguistically, a new world order of exclusion and inclusion, empowerment and disempowerment is emerging in post-Apartheid South Africa, and this exists among indigenous languages in South African Broadcasting Corporation (SABC). This thesis is an attempt to offer a sociolinguistic analysis of how the SABC television, with SABC 1 and SABC 2 as examples the public broadcaster’s shortcomings in implementing its own language policy. This has led to both SABC 1 and SABC 2 using languages in such a way that does not reflect the linguistic realities and linguistic demographics of South Africa. Furthermore, the thesis’ analysis has also established that there is an ongoing production and distribution of ideologies of whiteness in one of the SABC’s soap operas. These issues sum up the interest of this thesis. Ultimately, the thesis has reached a conclusion that the SABC language policy is failing the small-status linguistic and cultural groups in South Africa.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, School of Arts, University of the Witwatersrand, Johannesburg, 2021